Assessing Contrasting Approaches to Da'wah on Radio in Ilorin, Nigeria - Abdulwahab Danladi Shittu; Ibrahim Mubarak Olalekan (Research Synergy Foundation, 2023)
Contemporary scholars in Nigeria have duly acknowledged the significant role of electronic media in conveying the pure messages of Islam. Nevertheless, there exists variation in the approaches taken by advocates of Islam, resulting in diverse outcomes. This study undertook a comparative examination of two radio da'wah programs in Ilorin: